Targeting Lung Cancer Stem Cells: Research and Clinical Impacts - Zakaria, Norashikin; Satar, Nazilah Abdul; Halim, Noor Hanis Abu; Ngalim, Siti Hawa; Yusoff, Narazah Mohd; Lin, Juntang; Yahaya, Badrul Hisham (Frontiers Media, 2017)
Lung cancer is the most common cancer worldwide, accounting for 1.8 million new cases and 1.6 million deaths in 2012. Non-small cell lung cancer (NSCLC), which is one of two types of lung cancer, accounts for 85–90% of all lung cancers. Despite advances in therapy, lung cancer still remains a leading cause of death. Cancer relapse and dissemination after treatment indicates the existence of a niche of cancer cells that are not fully eradicated by current therapies. These chemoresistant populations of cancer cells are called cancer stem cells (CSCs) because they possess the self-renewal and differentiation capabilities similar to those of normal stem cells. Targeting the niche of CSCs in combination with chemotherapy might provide a promising strategy to eradicate these cells. Thus, understanding the characteristics of CSCs has become a focus of studies of NSCLC therapies.